2016
DOI: 10.1186/s12913-016-1384-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a community pharmacist-led medication review on medicines use in patients on polypharmacy - a prospective randomised controlled trial

Abstract: BackgroundIn 2010 the ‘Polymedication Check’ (PMC), a pharmacist-led medication review, was newly introduced to be delivered independently from the prescriber and reimbursed by the Swiss health insurances. This study aimed at evaluating the impact of this new cognitive service focusing on medicines use and patients’ adherence in everyday life.MethodsThis randomised controlled trial was conducted in 54 Swiss community pharmacies. Eligible patients used ≥4 prescribed medicines over >3 months. The intervention gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
118
0
19

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 49 publications
6
118
0
19
Order By: Relevance
“…Evidence has demonstrated the impact of clinical services for the community 18,19 . The purpose of pharmacotherapeutic monitoring/follow-up of users, and pharmacotherapeutic review, is evaluation of the medical drugs used by patients, prescribed and not prescribed, for the purpose of identifying drug interactions, or low levels of adherence to treatment, such as might be compromising the therapeutic results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated the impact of clinical services for the community 18,19 . The purpose of pharmacotherapeutic monitoring/follow-up of users, and pharmacotherapeutic review, is evaluation of the medical drugs used by patients, prescribed and not prescribed, for the purpose of identifying drug interactions, or low levels of adherence to treatment, such as might be compromising the therapeutic results.…”
Section: Discussionmentioning
confidence: 99%
“…The financial burden and detrimental clinical outcomes associated with these problems still needs resolution . Hence addressing this issue by establishing effective pharmaceutical care services in community pharmacies is vital …”
mentioning
confidence: 99%
“…Previous research has demonstrated the impact of community pharmacists in educating about and managing medications in patients who require polypharmacy [54], but studies have not been completed yet in the muscular dystrophy population. Such studies are needed.…”
Section: Discussionmentioning
confidence: 99%